THE ROLE OF JASMONIC ACID AND POTASSIUM NITRATE ON IN VITRO PRODUCATION OF MICROTUBERS OF TWO POTATO CULTIVARS - & Khalaf, Al-Amery (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The experiments were conducted at the plant tissue culture lab of the College of Agriculture, University of Baghdad to study the role of some culture medium components on the in vitro production of two cultivars of potato. Explants (tuber sprouts) excised from two cultivars of potato, Burren and Riviera, were surface sterilized with sodium hypochlorite at 1.5% and cultured on basal MS medium to obtain shoots. The obtained shoots were cultured on MS medium supplemented with BA and GA3 at 0.5 and 0.4 mg.L-1, respectively for shoot multiplication. Shoots were divided into 2-3 nodal segments and cultured on MS medium to promote microtubers formation, Shoot segments were cultured on MS medium supplemented with five concentrations of Jasmonic acid at 0, 0.5, 1, 1.5, and 2 mg.l-1 in combinations with Potassium nitrate at 0.5X, 1X, 1.5X and 2X from the recommended strength of KNO3 in MS medium. Results showed that Riviera cultivar cultured on MS medium supplemented with JA at 1 mg.L-1 and KNO3 at 1.5X gave the highest number of microtubers of 5.30 tuber.plant-1, tuber diameter of 9.15 mm, fresh weight of 0.59 g, dry weight percentage of 26.26%, and starch percentage of 19.40% while Burren cultivar cultured on MS media supplemented with two concentrations of JA at 1.5, 2 mg.L-1 and 2 mg.L-1 and KNO3 at 2X gave the most significant potassium percentage of 2.72%.The above results can be adopted on in vitro production of microtubers of Burren and Riviera potato cultivars successfully.